2016
DOI: 10.1016/j.ceca.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial remodeling: Rearranging, recycling, and reprogramming

Abstract: Asthma’s a problem of inhaling too much Hyperinflation, air trapping, and such. But physicians find themselves just as aghast When a patient finally exhales his last. So which deserves the frowning pout: Breathing in or breathing out? So it is with the mitochondrion, Which is better, fission or fusion? Both out and in make good respiration Ditto for mitochondrial undulation. Roberta A. Gottlieb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 218 publications
(228 reference statements)
0
58
0
2
Order By: Relevance
“…These mechanisms may include mitochondrial fission or fusion, in which damaged parts of mitochondria are excised and smaller mitochondria fuse to create larger mitochondria. 56,57 Drp1 is a pivotal protein in mediating mitochondrial fission as it has the capacity to constrict mitochondria. In the context of HCV infection, it has been demonstrated that mitochondrial localization of phosphorylated form of Drp1 protein (Drp1-Ser616) was a prelude to mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms may include mitochondrial fission or fusion, in which damaged parts of mitochondria are excised and smaller mitochondria fuse to create larger mitochondria. 56,57 Drp1 is a pivotal protein in mediating mitochondrial fission as it has the capacity to constrict mitochondria. In the context of HCV infection, it has been demonstrated that mitochondrial localization of phosphorylated form of Drp1 protein (Drp1-Ser616) was a prelude to mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
“…A role for mitochondria and ER is suggested in the latter process. Gottlieb and Bernstein [33] contribute an interesting review that discusses mitochondrial remodeling and mechanisms that govern its rearranging, recycling, and reprogramming. Mitochondria adapt to a wide range of cellular requirements, adjusting fuel utilization to meet ATP requirements and regulating ROS output.…”
Section: Ros and Intracellular Ca2+ Signalingmentioning
confidence: 99%
“…p62, which orchestrate organellar engulfment by the autophagosome. 31 The pro-apoptotic BH3-only proteins Bnip3 and Nix have recently been demonstrated to also function as adaptors for recruiting mitochondria to the autophagosome, by interacting with LC3. 32 In non-cardiac cell types, the adaptor proteins NDP52 and Optineurin have been found to participate in mitophagy, 33 undergoing recruitment to mitochondria in a Pink1-dependent but Parkin-independent manner.…”
Section: Cargo-selective Autophagy: Macro-autophagy Subtypesmentioning
confidence: 99%